STUDI LITERATUR PERAN P5 DALAM MEMPERKUAT KARAKTER KEWIRAUSAHAAN SISWA SMA - Roland Novrando Sirait; Nina Oktarina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This literature review research aims to analyze the role of the Pancasila Student Profile Strengthening Project (P5) in enhancing students' entrepreneurial character. Entrepreneurial character, which includes an innovative, creative, independent, calculated risk-taking, action-oriented, and value-creating mindset and behavior, is increasingly relevant in facing the challenges of the 21st century. P5, as part of the Merdeka Curriculum, is designed to develop various dimensions of student character through project-based learning and active engagement with the surrounding environment. This literature study examines the concept of entrepreneurial character in the educational context and the potential of P5 in fostering student character. Despite its promise, the implementation of P5 faces challenges such as a lack of teacher understanding and skills, resistance to change, and difficulties in character assessment. To optimize the role of P5 in strengthening entrepreneurial character, policy support, teacher professional development, and collaboration with the local community are necessary. This research concludes that P5 has significant potential in instilling entrepreneurial values through contextual and collaborative learning experiences, but its implementation requires well-planned strategies to overcome existing challenges.